Adapting theatrical decoration for two different theaters - mona elsers (Journal of Architecture, Art & Humanistic Science, 2024)

(untitled)
in the Azbakeya neighborhood within the activities of the theater festival for higher institutes and private academies within the framework of participation in the competition of the Ministry of Higher Education for the 7-color band for students of the Higher Institute of Applied Arts on the sixth of October. The text was written by Salim Kitchener, and revolves around The events of the play are in an absurd framework that tends to symbolism, as it revolves around Antar Ibn Shaddad from the era of pre-Islamic era, coincidentally speaking to him with Shayboub, as they move through time and reach our present era.After reading and analyzing the text and attending several rehearsals for the presentation and discussion with the director, it was agreed to deal with the show in an absurd manner that tends to symbolism, because the text is based on a fantasy idea whose events are inspired by the author's imagination. The researcher identified the main problem, which is: How to create an actual image on the stage that moves the spectator from the era of ignorance to our present time and from place to place where events move six different scenes until they end up in a mental hospital and achieve this despite the weak budget because the show is an activity My students on a limited budget?The researcher wondered, is it possible to find a quick way to implement the decoration and change the scenes to move the spectator from one scene to another without feeling the events stopped or leaving the absurd dramatic atmosphere? Finally, is it possible to design and implement a decor suitable for displaying the text on two theaters, each of which differs in standards and specifications, as the novel was shown on the Romance Theater in May 2018, and then the El-Sawy Culture Wheel Theater in Cairo, Zamalek District, in July 2018?Consequently, the researcher designed a decor in an absurd manner that tends to symbolism, as Antara Ibn Shaddad travels through time from the era of ignorance to our present time and moving from place to place until they end up in a mental hospital, and they do not believe the extent of human degeneration in moral values and humanity.